Monitoreo de equipos electrógenos a través del Web Server del PLC S7-1200. - Silva Quezada, Servio Vicente (2022)
This degree project explains the development of a monitoring system through an Internet of Things platform; which collects, stores and visualizes the functional or operational status of a genset, especially the temporary states of the internal combustion engine sensors such as: coolant temperature, oil pressure, fuel level and battery voltage. This system constantly evaluates each of the sensors, takes their values and compares them with the appropriate nominal values conditioned in the programming. When the monitored values are out of the permissible ranges, the system prevents starting, it stops the genset and/or issues a warning by e-mail. Additionally, it evaluates the presence of conventional mains power and if the sensor reading is correct and there is no conventional power, it starts up. Tia PORTAL software was used as a programming tool and the PLC S7-1200 and SM 1234 AI/AQ were used for data acquisition. For sending the data to the cloud, SIMATIC IOT 2040 was used, which through the RED Node with the Ubidots Out node is linked to the Ubidots Internet of Things platform. Sensor information is displayed in real time via a dashboard on an Ubidots IoT platform from any device with Internet access, facilitating long-distance monitoring. This project focuses on the new era of Industry 4.0 where electromechanical engineers can contribute to the development of industrial automation. KEYWORDS: monitoring system, TIA Portal V16, IOT 2040, Node RED, dashboard, Ubidots.